Simulation Analysis of Large Diameter Shield Cutting through Diaphragm Wall Impact on Metro Station Deformation - YUAN Xiao; LI Zhanglin; HE Guojun; ZHANG Mengxi; ZHAO Huiling (Chengshi guidao jiaotong yanjiu)
［Objective］ Cutting through the existing underground structure in the process of shield tunneling will cause adverse effects on the structure. Therefore, it is necessary to study the consequent deformation of the structure and the stratum caused by shield tunneling. ［Method］ Based on the actual project of the super-large diameter shield tunnel of Nanjing Jianning West Road river-crossing passage that cuts through the diaphragm wall of the existing metro station, a three-dimensional numerical model of tunnel-station-stratum is established, to study the ground settlement and the deformation of the station structure when the tunnel cuts through the diaphragm wall and pile foundation of the station. ［Result & Conclusion］ The simulation research results show that the station pile foundation has a significant effect on settlement control. After the shield tunneling cuts off the lower part of the pile, a large settlement occurs on the ground surface above the incision. After the diaphragm wall being cut through, a settlement trough forms centered on the cut place of the wall, resulting in uneven settlement. The shield cutting through the underground diaphragm wall of the station causes differential settlement of two rails on the operating metro line, but still within the range of safety control index. The predictive results of this simulation analysis can provide a reference for the following construction and monitoring of this project, as well as for the construction optimization of similar shield tunnels cutting through existing underground engineering.